Characteristics and Mechanisms of the Sudden Warming Events in the Nocturnal Atmospheric Boundary Layer： A Case Study Using WRF - 马媛媛 杨毅 胡小明 甘茹蕙 (Acta meteorologica Sinica, 2015)
Although sudden nocturnal warming events near the earth＇s surface in Australia and the United States have been examined in previous studies, similar events observed occasionally over the Loess Plateau of Northwest China have not yet been investigated. The factors that lead to these warming events in such areas with their unique topography and climate remain not clear. To understand the formation mechanisms and associated thermal and dynamical features, a nocturnal warming event recorded in Gansu Province （northwest of the Loess Plateau） in June 2007 was investigated by using observations and model simulations with the Weather Research and Forecasting （WRF） model. Observations showed that this near-surface warming event lasted for 4 h and the temperature increased by 2.5℃. During this event, a decrease in humidity occurred simultaneously with the increase of temperature. The model simulation showed that the nocturnal warming was caused mainly by the transport of warmer and drier air aloft downward to the surface through enhanced vertical mixing. Wind shear played an important role in inducing the elevated vertical mixing, and it was enhanced by the continuous development of the atmospheric baroclinicity, which converted more potential energy to kinetic energy.